Stress Management as a component of Work-life Balance with regards to a select field - SRAVANI, AMUDA (IJRDO - Journal of Applied Management Science, 2018)
Work-life balance is the term used to describe those practices that employees do to achieve a balance between the demands of the employee’s family (life) and work lives. Wherein, the organisation plays a vital role in achieving the balance. Work-life balance is about people having a measure of control over when, where and how they work. It can only be achieved when an individual’s right to fulfill the personal life needs and also working life needs, which are accepted and respected as the norm within the organisation. This mutually benefit all the three i.e., the individual, business and society. The concept of work-family life balance has emerged from the acknowledgement that an individual’s work-life and personal/family life may expert conflicting demand on each other. Conflict is a normal part of life and is a natural result of conflicting demands arising from multiple roles such as mother, daughter, daughter-in-law, wife, friend and employee. In order to manage the negative spillover of conflict, it is important to balance the demands from both domains.